Seemings and Defeat by Disagreement in the Case of Religious Experience: Comments on Harold Netland's Book Religious Experience and the Knowledge of God - Geivett, R. Douglas (Philosophia Christi, 2023)
Exploiting the resources of phenomenal conservatism, Harold Netland has offered a "critical-trust" approach to assessing the veridicality of religious experience and to ascertaining its evidential force in relation to Christian theistic belief. I suggest that, if we give seemings carried in religious experience their epistemic due, it may turn out that religious experience is practically universal and that the potential defeat of justification for religious belief by disagreement among purported epistemic peers is itself defeated by the private character of seemings in the religious experiences of believers.